The effect of sport consumption on citizens national pride and subjective well-being - Silva, Alfredo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The objective of this study was to disentangle the relationships that exist between sporting success, sports consumption (i.e., sport participation, sport spectating and sport media viewing), national pride and subjective well-being. Data was collected from 374 respondents. Structural Equation Modelling was used to analyse the variables that were measured in accordance with previous studies. The model which centred on sports consumption showed a great explanatory capacity (73% and 43%). Sport participation was the factor with the highest impact on national pride and subjective well-being, even greater than the effects of sporting success and sport spectating. Another reason for the importance of citizens being physically active was noted. These results have managerial implications for sports policymakers and managers responsible for national teams and sport participation programmes. No evidence was found that higher levels of national pride directly affect subjective well-being.